Monsoon Surges Enhance Extreme Rainfall by Maintaining the Circulation of Landfalling Tropical Cyclones and Slowing Down Their Movement - Zhao, Dajun; Chen, Lianshou; Yu, Yubin (Frontiers in Earth Science, 2021)
Extreme rainfall induced by landfalling tropical cyclones (ERLTCs) in China can cause flash floods and other disastrous impacts, so investigating their genesis and mechanism of enhancement has been attracting considerable attention. This study demonstrates that the extreme rainfall of landfalling tropical cyclones (LTCs) possesses two key properties—namely, maintenance of the LTC circulation and a lagging (slowing down or looping) of its movement, and the monsoon surge can provide a positive contribution to these properties. Specifically, diagnostics show that the low-level cyclonic vorticity and upper-level divergence of ERLTCs are significantly stronger than those of NERLTCs (non-extreme-rainfall-producing LTCs). The continuous intensification of the cyclonic rotation in the lower troposphere before the occurrence of extreme rainfall is a significant feature that distinguishes ERLTCs from NERLTCs. Vorticity budget analysis further shows that the relative vorticity advection term contributes the most to the local increase and maintenance of vorticity in the middle and lower troposphere of ERLTCs under the influence of the southwest monsoonal surge, thus demonstrating that the monsoonal surge favors the maintenance of LTC circulation. On the other hand, the activity of the southwest monsoonal surge is mainly manifested in the zonal wind anomaly, and the corresponding strong westerly transport can significantly reduce the zonal component of the steering flow. As a result, the total steering flow can be weakened, which decreases the northwestward translation speed of ERLTCs, and thus the monsoonal surge favors a lagging (slowing down or looping) of LTC movement. These results reveal the mechanism of influence through which the monsoonal surge affects ERLTCs via its direct impacts on the maintenance of their circulation and lagging of their movement—two distinct evolutionary characteristics.